#144 Pharmacological investigation of antimicrobial, analgesic and antiinflammatory activity of Physalis angulata L. fruit extract in experimental animal model - Jena, Rasmita; Rath, Diptirani; Kar, Durga Madhab (Journal of Pharmaceutical Chemistry, 2022)
Physalis angulata L. (Solanaceae) is an indigenous medicinal herb that has been recommended for fever, sore throat, pain, malaria, asthma, cuts, wounds, obstructive urination, diabetes, cancer, earache, etc. The research aimed to screen the phytoconstituents and evaluate the toxicity profile, antimicrobial, analgesic, and anti-inflammatory activity using various experimental animal models. Air-dried fruit powder sample was defatted with petroleum ether and extracted with methanol using the Soxhlet apparatus. Again the samples were macerated with distilled water to obtain the aqueous extract. The phytochemical screening was performed as per the standard methods. Antimicrobial activity was assessed by the agar well diffusion method using microbial strains like B. cerues, E. coli, S. aureus. Healthy Swiss albino Wistar rats of either sex weighing 180-200 gm were selected for this experiment as per the approval of the Institutional Ethics Committee. The acute oral toxicity was performed as per the OECD guidelines 423 to evaluate the safety profile of the extracts. The analgesic and anti-inflammatory activity were studied at two different doses (200 mg/kg and 400 mg/kg body weight) in the different models using Wistar albino rats. The crude extracts confirmed the presence of alkaloids, steroids, flavonoids, phenols, saponins, tannins, glycosides, etc. 400 mg/kg body weight was found to be safe for oral administration. In the antimicrobial study, methanol extract showed the highest zone of inhibition against the tested S. aureus (29 mm), and aqueous extract showed the least inhibition. The results revealed that only 400 mg/kg of methanol extract has statistically significant (p < 0.05) analgesic activity in the hot-plate model and tail-flick model. The higher dose of methanol extract significantly decreased the no. of writhing in the acetic acid-induced writhing model. 200 mg/kg and 400 mg/kg body weight dose of methanol extract had significant anti-inflammatory activity in terms of %inhibition of paw edema in carrageenan model compared to aqueous at 3 h and 4 h. Hence, the herb P. angulata L. might be considered as a budding candidate for bioactivity-guided isolation of natural anti-inflammatory and analgesic agents.